The Influence of Organizational Culture on the Performance of Educators in Private Madrasahs - Muhammad Aji Santoso; Riza Kurnia; Rohani; Arvin Efriani; Fajri Ismail (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to analyze the influence of organizational culture on the performance of educators at MI Munawariyah Palembang. The background of the research is based on the importance of organizational culture in enhancing the professionalism of educators in Islamic educational institutions. The objective of the study is to determine the extent of the influence of organizational culture on educator performance. The research uses a quantitative approach with a correlational design and a saturated sampling technique. The research population includes all educators at MI Munawariyah Palembang, with a sample of 35 teachers. The research instrument employed a Likert scale questionnaire, which was tested for validity and reliability, and analyzed using simple linear regression. The results indicate that organizational culture has a significant effect on educator performance, with a contribution of 65.2%, represented by the regression equation Y = 3.245 + 0.672X and a significance level of 0.000. The study concludes that organizational culture is an important factor in improving the performance of educators in Islamic educational institutions.